Functional Effects of ARV-1502 Analogs Against Bacterial Hsp70 and Implications for Antimicrobial Activity - Brakel, Alexandra; Kolano, Lisa; Kraus, Carl N.; Otvos, Laszlo; Hoffmann, Ralf (Frontiers in Chemistry, 2022)
The antimicrobial peptide (AMP) ARV-1502 was designed based on naturally occurring short proline-rich AMPs, including pyrrhocoricin and drosocin. Identification of chaperone DnaK as a therapeutic target in Escherichia coli triggered intense research on the ligand-DnaK-interactions using fluorescence polarization and X-ray crystallography to reveal the binding motif and characterize the influence of the chaperone on protein refolding activity, especially in stress situations. In continuation of this research, 182 analogues of ARV-1502 were designed by substituting residues involved in antimicrobial activity against Gram-negative pathogens. The peptides synthesized on solid-phase were examined for their binding to E. coli and S. aureus DnaK providing 15 analogs with improved binding characteristics for at least one DnaK. These 15 analogs were distinguished from the original sequence by their increased hydrophobicity parameters. Additionally, the influence of the entire DnaK chaperone system, including co-chaperones DnaJ and GrpE on refolding and ATPase activity, was investigated. The increasingly hydrophobic peptides showed a stronger inhibitory effect on the refolding activity of E. coli chaperones, reducing peptide refolding by up to 64%. However, these more hydrophobic peptides had only a minor effect on the ATPase activity. The most dramatic changes on the ATPase activity involved peptides with aspartate substitutions. Interestingly, these peptides resulted in a 59% reduction of the ATPase activity in the E. coli chaperone system whereas they stimulated the ATPase activity in the S. aureus system up to 220%. Of particular note is the improvement of the antimicrobial activity against S. aureus from originally >128 µg/mL to as low as 16 µg/mL. Only a single analog exhibited improved activity over the original value of 8 µg/µL against E. coli. Overall, the various moderate-throughput screenings established here allowed identifying (un)favored substitutions on i) DnaK binding, ii) the ATPase activity of DnaK, iii) the refolding activity of DnaK alone or together with cochaperones, and iv) the antimicrobial activity against both E. coli and S. aureus.